Evaluating Maize Hybrids for Yield, Stress Tolerance, and Carotenoid Content: Insights into Breeding for Climate Resilience - Călin Popa; Roxana Elena Călugăr; Andrei Varga; Edward Muntean; Ioan Băcilă; Carmen Daniela Vana; Ionuț Racz; Nicolae Tritean; Ioana Virginia Berindean; Andreea D. Ona; Leon Muntean (Plants)
To ensure food and feed security, modern maize hybrids must not only perform well under changing climate conditions but also consistently achieve higher and stable yields, exhibit maximum tolerance to stress factors, and produce high quality grains. In a study conducted in 2022 and 2023, 50 maize hybrids were developed from crosses of five elite (highly productive) inbred lines and ten lines possessing favorable genes for carotenoid content. These hybrids were tested under particularly unfavorable conditions for maize cultivation. The aim was to identify which lines effectively transmit the desired traits to the offspring (general combining ability—GCA), and to identify superior hybrids in terms of productivity, adaptability, and quality (specific combining ability—SCA). The study revealed that total carotenoids ranged from 2.30 to 40.20 μg/g for the inbred lines and from 7.45 to 25.08 μg/g for hybrids. A wider distribution of values was observed in the inbred lines compared to the hybrids for key carotenoids such as lutein, zeaxanthin, β-cryptoxanthin, and β-carotene. Among the hybrids, notable performers in yield, adaptability, and carotenoid content included E390×D302, A452×D302, and A447×D302. The paternal inbred line D302 exhibited a high general combining ability for yield (1446 kg ha−1) and, when crossed with several inbred lines, produced hybrids with enhanced yields and higher levels of zeaxanthin, lutein, and β-carotene, as well as improved unbroken plants percent.